Textbook on nutrition and dietetics for post basic BSc Nursing students - Clement, I. (Jaypee Brothers Medical Publishers (P) Ltd, 2015)
Textbook on Nutrition and Dietetics is prepared to meet the requirement as per the Indian Nursing Council recommendations. This book is divided into four sections: first-nutrition, second-dietetics, third-infant and child nutrition, and fourth-community nutrition, and contains 32 chapters. For better understanding of the content, each chapter has the glossary, illustrations done with simple lucid language, and with adequate tables and diagrams wherever needed. For students' betterment, previous years' question papers (six in number) have also been provided. Be it the students or teachers, whosoever goes through this book, is sure to get clear-cut knowledge about the concept of nutrition and dietetics